2021
DOI: 10.1002/tox.23299
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide reduces the expression of E2F1, cyclin E, and phosphorylation of PI3K signaling molecules in acute leukemia cells

Abstract: Arsenic trioxide (ATO) has been used for the treatment of acute promyelocytic leukemia (APL). Although ATO modulates cell cycle progression and apoptosis in APL cells, its exact mechanism of action remains elusive. In this research, we investigated its effects on E2F1, cyclin E, p53, pRb, and PI3K signaling molecules by western blotting, immunocytochemistry and/or confocal imaging. We found that ATO inhibited the proliferation of APL cells through down‐regulation of E2F1 and cyclin E expression, and stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…From our previous study, we found that ATO activates p53 through a downregulation of complex molecules in the tissues of APL mice 47 . Our new findings reveal that CDDP treatment significantly disrupted MDM2‐DAXX‐HAUSP and downregulated the association and expression of its constituents/molecules in NB4 cells, KG1a cells, and APL mice liver tissue (Figure 3A–E).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…From our previous study, we found that ATO activates p53 through a downregulation of complex molecules in the tissues of APL mice 47 . Our new findings reveal that CDDP treatment significantly disrupted MDM2‐DAXX‐HAUSP and downregulated the association and expression of its constituents/molecules in NB4 cells, KG1a cells, and APL mice liver tissue (Figure 3A–E).…”
Section: Discussionsupporting
confidence: 57%
“…2,4,[13][14][15][16] From our previous study, we found that ATO activates p53 through a downregulation of complex molecules in the tissues of APL mice. 47 Our new findings reveal that CDDP treatment significantly disrupted MDM2-DAXX-HAUSP and downregulated the association and expression of its constituents/molecules in NB4 cells, KG1a cells, and APL mice liver tissue (Figure 3A-E). Several other studies have provided evidence that DNA damage and stress signal is transmitted from protein kinase (ATM and ATR) and its downstream CHK1 and CHK2 target phosphorylation at different residues in cancer cells.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, ATO has been shown to suppress anti-apoptotic genes (e.g., survivin, bcl-2 and Mcl-1) and to upregulate pro-apoptotic genes (e.g., Puma, Bax and NOXA) in various tumor cell lines, such as leukemia, glioma and rhabdomyosarcoma [9][10][11]. Furthermore, ATO regulates the expression of proteins implicated in cell cycle control and differentiation (e.g., p21 WAF1/KIP1 , p53, E2F1, HoxC9, cyclin E and D) [12][13][14]. Moreover, ATO has been reported to suppress angiogenesis by inhibiting pro-angiogenic factors, such as vascular endothelial growth factor (VEGF), Notch1 and VEGFR-2 [15,16].…”
Section: Introductionmentioning
confidence: 99%